Macroeconomic Determinants of Wage Adjustments in White-Collar Occupations - Nichols, Donald A. (The Review of Economics and Statistics, 1983)
T HERE is no professional consensus about the process of aggregate wage inflation. A spectrum of opinion exists between the following extreme poles: (1) That wages are determined instantaneously in markets where participants have rational expectations and can anticipate in their behavior the long-run consequences of any consistent pattern of macro policy making;' and (2) that wages are determined largely by institutional forces including considerations of equity, normal historical wage patterns, union strength, and current bargaining conditions.2 Adherents of these polar positions have little respect for wage adjustment equations of the Phillips (1958) or Phelps (1967)-Friedman (1968) variety in which wages are related structurally to aggregate unemployment rates. These adjustment equations occupy a middle ground in the spectrum and are currently used in large scale econometric models to explain how the effects of a change in demand are distributed into real and price components. Between the poles are several alternative justifications of wage-unemployment relationships. Among these are the following views: That wages are determined as in (1) above except for the existence of long-run contracts;3 that the determination of expectations about future prices can be fairly approximated by a distributed lag on past prices;4 that it is past prices rather than expectations of future prices that are important;5 and that economic conditions are but one of a set of factors to be included in the current bargaining conditions that determine wages.6 Which of these views best describes the process of wage determination is an empirical question, but the question is quite complicated and does not appear to be capable of resolution through a single, conclusive test. Many issues are involved simultaneously and no one has been able to find a set of workable assumptions that can be agreed upon by all as being a sensible way to proceed. The question of wage determination continues to divide macroeconomic opinion more than any other single issue. This paper reports results of empirical work on wage equations in which a strategy of disaggregation has been followed. It is part of a larger project to estimate the dependence of the natural rate of unemployment on the distributions of the supply and demand for labor according to location and occupation. As an estimation strategy, disaggregation can avoid problems of identification and could, in principle, provide a way to distinguish among the many competing hypotheses in this area. In practice, the disagreements are so fundamental and the possible tests so limited that the results can be offered as no more than an extension of the wage equation literature rather than as a resolution of the issue of whether wage equations should be treated as structural relations or, of even greater ambition, what those relations might be. The extension provided follows the direction of Baily and Tobin (1977, 1978) who hypothesized that the rate of wage change in a single labor force group should depend on the unemployment rate of that group and its wage relative to the wages of other groups. The results are interesting for several reasons. First, the wage data that are used in these tests come from a survey not previously used in the estimation of aggregate wage equations. The data are from the National Survey of Professional Administrative, Technical and Clerical Pay (PATC).7 This survey is conducted annually by the Bureau Received for publication September 18. 1981. Revision accepted for publication May 4, 1982. * The University of Wisconsin. The author wishes to thank Gregory Krohn and Bruce Chapman for their excellent research assistance. Helpful comments were received from Paul Gertler and the participants at a seminar at the National Commission for Employment Policy. This research was supported by Grant Number 99-0-2289-50-11 from the National Commission for Employment Policy, and Contract Number 20-06-08-11 from the Employment and Training Administration, U.S. Department of Labor. ' See, for example, Lucas (1973) and Sargent and Wallace (1975). 2See Dunlop (1977). 3See Phelps and Taylor (1977) and Fischer (1977). 4McNees (1979) provides a way to distinguish this position from the one in the subsequent phrase. 5 See Okun (1978) for a summary of studies of this kind. 6See Hicks (1955) and (1974, pp. 59-85). Bureau of Labor Statistics (1980).